The need for Streamlining the Public Expenditure Management of Kerala - V Johnson (RESEARCH REVIEW International Journal of Multidisciplinary, 2018)
Over the past couple of decades, the financial squeeze in the state of Kerala has become a major issue in the academic narratives, policy analysis and in the everyday discourses. For the Government of Kerala, it is high time to act upon the fiscal strainby initiating radical reforms aiming at revamping the existing system of Public Expenditure Management Practices (PEM) in the state. Drawing from the success stories of PEM reforms initiated in countries like New Zealand, the state Government shall look into the possibility of adopting accrual based accounting, private sector style management practices and professionalism while strengthening the budgeting and auditing process. The legal and administrative impediments hampering the speedy implementation of the reform process also have to be addressed with due importance, before any blatant disasters occur.